2022
DOI: 10.1111/trf.16895
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusions in a murine model of neonatal polymicrobial sepsis: Divergent effects on inflammation and mortality

Abstract: Background Platelet transfusions (PTxs) are often given to septic preterm neonates at high platelet count thresholds in an attempt to reduce bleeding risk. However, the largest randomized controlled trial (RCT) of neonatal transfusion thresholds found higher mortality and/or major bleeding in infants transfused at higher thresholds. Using a murine model, we investigated the effects of adult PTx on neonatal sepsis‐induced mortality, systemic inflammation, and platelet consumption. Study design and methods Polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…Thrombocytopenia is typically defined as a platelet count <150 000 platelets/µL of blood in humans and is common in preterm and low-birth-weight neonates, affecting 18% to 35% of neonatal intensive care unit patients. 1 There are conflicting data on whether the degree of thrombocytopenia is associated with major bleeding risk in neonates and on whether neonatal platelet transfusions increase or decrease the risk of major bleeding episodes. 2–4 A recent study of 1221 preterm infants noted a lower platelet count was significantly associated with increased risks of hemorrhage and mortality, 2 but whether platelet transfusions are beneficial in neonates may be dependent on many factors.…”
mentioning
confidence: 99%
“…Thrombocytopenia is typically defined as a platelet count <150 000 platelets/µL of blood in humans and is common in preterm and low-birth-weight neonates, affecting 18% to 35% of neonatal intensive care unit patients. 1 There are conflicting data on whether the degree of thrombocytopenia is associated with major bleeding risk in neonates and on whether neonatal platelet transfusions increase or decrease the risk of major bleeding episodes. 2–4 A recent study of 1221 preterm infants noted a lower platelet count was significantly associated with increased risks of hemorrhage and mortality, 2 but whether platelet transfusions are beneficial in neonates may be dependent on many factors.…”
mentioning
confidence: 99%
“…However, it is unclear whether these short-term morbidities fully explain the worse long-term neurodevelopmental outcomes or whether transfused platelets have direct harmful effects on the developing brain. It is now recognized that, in addition to their important hemostatic functions, platelets are active participants in immune and inflammatory responses, and recent animal studies have reported that platelet transfusions can alter neonatal immune responses . It is therefore possible that transfused platelets may have direct proinflammatory effects on the preterm brain, although this remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…In a neonatal model of polymicrobial sepsis (using the cecal slurry model), cecal slurry batches differed substantially in their bacterial composition and sepsis-related mortality. Interestingly, platelet transfusions (from adult donors) increased the mortality and the systemic inflammatory response (plasma cytokines) of postnatal day 10 (P10) newborn mice infected with a low-mortality batch, but attenuated the inflammatory response and decreased the mortality of newborn mice infected with a high-mortality batch [49 ▪ ]. These findings demonstrated that platelet transfusions can have either pro-inflammatory or anti-inflammatory effects in sepsis, depending on the type and/or severity of the infectious stimulus.…”
Section: Platelet Transfusions In Neonatesmentioning
confidence: 99%